Inhibition of USP10 induces degradation of oncogenic FLT3 - Weisberg, Ellen L; Schauer, Nathan J; Yang, Jing; Lamberto, Ilaria; Doherty, Laura; Bhatt, Shruti; Nonami, Atsushi; Meng, Chengcheng; Letai, Anthony; Wright, Renee; Tiv, Hong; Gokhale, Prafulla C; et al. (Nature chemical biology, 2017)
An inhibitor of the deubiquitinase (DUB) USP10 regulates the degradation of oncogenic FLT3, thus defining USP10 as a DUB for FLT3 and providing a therapeutic approach for human acute myeloid leukemia in which FLT3 activation is dysregulated. Oncogenic forms of the kinase FLT3 are important therapeutic targets in acute myeloid leukemia (AML); however, clinical responses to small-molecule kinase inhibitors are short-lived as a result of the rapid emergence of resistance due to point mutations or compensatory increases in FLT3 expression. We sought to develop a complementary pharmacological approach whereby proteasome-mediated FLT3 degradation could be promoted by inhibitors of the deubiquitinating enzymes (DUBs) responsible for cleaving ubiquitin from FLT3. Because the relevant DUBs for FLT3 are not known, we assembled a focused library of most reported small-molecule DUB inhibitors and carried out a cellular phenotypic screen to identify compounds that could induce the degradation of oncogenic FLT3. Subsequent target deconvolution efforts allowed us to identify USP10 as the critical DUB required to stabilize FLT3. Targeting of USP10 showed efficacy in preclinical models of mutant-FLT3 AML, including cell lines, primary patient specimens and mouse models of oncogenic-FLT3-driven leukemia.